High-throughput and genome-scale targeted mutagenesis using CRISPR in a nonmodel multicellular organism, Bombyx mori - Ma, Sanyuan; Zhang, Tong; Wang, Ruolin; Wang, Pan; Liu, Yue; Chang, Jiasong; Wang, Aoming; Lan, Xinhui; Sun, Le; Sun, Hao; Shi, Run; Lu, Wei; et al. (Genome Research, 2024)
Large-scale genetic mutant libraries are powerful approaches to interrogating genotype–phenotype correlations and identifying genes responsible for certain environmental stimuli, both of which are the central goal of life science study. We produced the first large-scale CRISPR-Cas9-induced library in a nonmodel multicellular organism, Bombyx mori. We developed a piggyBac-delivered binary genome editing strategy, which can simultaneously meet the requirements of mixed microinjection, efficient multipurpose genetic operation, and preservation of growth-defect lines. We constructed a single-guide RNA (sgRNA) plasmid library containing 92,917 sgRNAs targeting promoters and exons of 14,645 protein-coding genes, established 1726 transgenic sgRNA lines following microinjection of 66,650 embryos, and generated 300 mutant lines with diverse phenotypic changes. Phenomic characterization of mutant lines identified a large set of genes responsible for visual phenotypic or economically valuable trait changes. Next, we performed pooled context-specific positive screens for tolerance to environmental pollutant cadmium exposure, and identified KWMTBOMO12902 as a strong candidate gene for breeding applications in sericulture industry. Collectively, our results provide a novel and versatile approach for functional B. mori genomics, as well as a powerful resource for identifying the potential of key candidate genes for improving various economic traits. This study also shows the effectiveness, practicality, and convenience of large-scale mutant libraries in other nonmodel organisms.
10.1101/gr.278297.123